The equation is:
-5(2x - 3) + 4x = -3x + 6
To solve for x, we first need to simplify the equation:
-10x + 15 + 4x = -3x + 6
Next, we combine like terms:
-10x + 4x - 3x = 6 - 15
Simplifying further:
-9x = -9
To isolate x, we divide both sides of the equation by -9:
x = 1
Therefore, the value of x that makes the equation true is 1.
Math Equation Response Question
What is the value of x that makes this equation true?
-5(2x-3)+ 4x = -3x+6
Use the on-screen keyboard to complete the equation below.
$$
1 answer